Unpredicted late-, new-onset thrombocytopenia and hypofibrinogenemia in Fab antivenom-treated rattlesnake envenomation. (September 2020) - Seifert, S.A.; Mascarenas, D.N.; Fullerton, L.; Warrick, B.J.; Smolinske, S.C.
Abstract: The use of Fab antivenom (Crotalidae Polyvalent Immune Fab (Ovine) (CroFab); Boston Scientific) against North American Crotalidae envenomation is associated with the development of late- (≥4 days post-envenomation), new-onset of hematological abnormalities. Although attempts have been made to identify predictive indicators during the acute phase of an envenomation, of patients who are not at-risk of late-, new-onset of hematological abnormalities, there has been at least one prior report of a patient who developed thrombocytopenia that was unpredicted by current indicators. We add three cases of unpredicted, late-, new-onset of hematological abnormalities in patients with Fab-treated rattlesnake bite. Highlights: Fab antivenom is associated with late-, new-onset hematological abnormalities. Predictors for absence of post-discharge hematologic risk have not been validated. Exceptions to predictors have been found. We add three additional cases of unpredicted, late hematologic abnormalities. All Fab-treated patients should be followed with lab for at least one week.